Cost-minimization analysis of oral and intravenous administration of linezolid in a public hospital in southern Brazil - Érika Taguti; Edson Antonio Alves da Silva; Andréia Cristina Conegero Sanches (São Paulo State University (UNESP), 2015)
Due to the paucity of cost-minimization studies about linezolid, the aim of this study was to estimate the cost differential between intravenous and oral administration. A retrospective cohort study and costminimization analysis was conducted between August 2009 and August 2013 in a public hospital in southern Brazil. Inpatient records were evaluated for 152 patients who received linezolid intravenously or orally. Over two-thirds of the patients (103, 67.8%) received the antibiotic by the intravenous route only (IV group), and the remainder received the antibiotic both routes sequentially (mixed group). In the IV group, 33 patients (31.7%) were eligible to receive the antibiotic orally. The total cost per patient (mean) after changing from intravenous to oral administration was significantly lower than the real cost paid per patient (mean) (p<0.001). The cost savings associated with switching to oral linezolid administration would be US$14,328.32 over four years. Pharmacoeconomic analyses of linezolid therapy can inform hospitals' decisions about the rational use of therapeutics and economic resources.